Morpho-anatomical and fingerprinting study of Vernonanthura patens (Kunth) H. Rob. - Patricia I. Manzano; Migdalia Miranda; Yamilet Gutiérrez; Efren Santos; Ramón Scull (GarVal Editorial Ltda., 2014)
Context: The specie Vernonanthura patens (Kunth) H. Rob. (Asteraceae) is a South American native wild bush that grows in various provinces of Ecuador and it has been used in traditional medicine for several diseases, highliting its use in treatment of leishmaniasis, a condition of high incidence in the country. Despite its medicinal use, there are few or none botanic, chemical nor biological studies for this species. Aims: In this paper it were comprised the morpho-anatomical characterization of leaves and stems and genetic identification of a DNA fraction of the leaves of V. patens, in order to provide the elements for proper characterization and contribute to the establishment of quality control. Methods: The macromorphological description was made in leaves and stems from the fresh plant. The micromorphological evaluation was performed by paraffin inclusion of the material with cross-section that were clarify in sodium hypochlorite for its posterior safranin and cresil's blue stained and its glycerinated gel fixation respectively. On obtaining the DNA chloroplast it was followed the internal protocol established by Molecular Biology CIBE´s laboratory. In order to sequence isolated DNA fragments from leaves of V. patens, Macrogen Maryland, USA´S company services were hired. Results: Leaves and stems of the new specie's micro morphological characteristics were described for the first time and new macro morphological characters were described too from stems particularly. Conclusions: Using molecular and macro-micromorphological assessments is corroborated the identity of the V. patens species growing in Ecuador coast.